1974
DOI: 10.1111/j.1399-3054.1974.tb03695.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Stress Response in Tomato (Lycopersicon esculentum) 1. Sites of Fe Reduction, Absorption and Transport

Abstract: T3238fer (Fe-inefficient) and T3238FER (Fe-efficient) tomato plants differ in their ability to utilize Fe and therefore can be used as test genotypes to locate sites of Fe uptake or to characterize changes that occur in roots in response to Fe stress (Fe deficiency). T3238fer does not respond to Fe stress. Release of hydrogen ions and reduction of Fe^+ to Fe^+ are two primary responses of T3238FER roots to Fe stress. Fe reduction sites were predominately in the young lateral roots, and between the regions of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
1

Year Published

1979
1979
2006
2006

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(54 citation statements)
references
References 11 publications
2
50
0
1
Order By: Relevance
“…Moreover, roots of peanut in mixture with maize produced more lateral roots than those grown in monoculture. The root tip regions of young lateral roots have been reported to be more active than other root areas in Fe reduction [20] and proton extrusion. [21,22] It is therefore conceivable that the higher exudation of Fe-reducing and Fe-chelating compounds by peanut roots reported here may have been concomitant with greater root branching and=or a larger production of lateral roots for plants in mixed culture.…”
Section: Role Of Root Morphology Of Peanut Intercropped With Maize Inmentioning
confidence: 99%
“…Moreover, roots of peanut in mixture with maize produced more lateral roots than those grown in monoculture. The root tip regions of young lateral roots have been reported to be more active than other root areas in Fe reduction [20] and proton extrusion. [21,22] It is therefore conceivable that the higher exudation of Fe-reducing and Fe-chelating compounds by peanut roots reported here may have been concomitant with greater root branching and=or a larger production of lateral roots for plants in mixed culture.…”
Section: Role Of Root Morphology Of Peanut Intercropped With Maize Inmentioning
confidence: 99%
“…The most promising clues on the regulation of strategy I are expected from the identification of the fer gene. The fer (T3238fer) mutant is not able to switch on strategy I responses after iron deficiency, such as enhanced extrusion of protons and Fe(III)-chelate reductase activity in the root (15,16). Reciprocal grafting of the mutant to a wild type indicated that the fer gene is required in roots but not in shoots (15).…”
mentioning
confidence: 99%
“…A promising clue about signaling components involved in iron acquisition was recently derived from the molecular identification of the tomato fer gene encoding a root-specific bHLH protein (25). The tomato fer mutant is unable to develop physiological and morphological iron-deficiency responses such as iron reduction and induced Leirt1 transporter gene expression in roots and accumulates less iron than wild type, leading to severe chlorosis (25)(26)(27). The fer gene seems to be required for sensing iron availability in the root tip and subsequently regulating the appropriate physiological and morphological responses (25).…”
mentioning
confidence: 99%